2021
DOI: 10.4085/301-20
|View full text |Cite
|
Sign up to set email alerts
|

Shoulder Strength and Range of Motion in Healthy Collegiate Softball Players

Abstract: Context: Shoulder range of motion (ROM) and strength are key injury evaluation components for overhead athletes. Most normative values are derived from male baseball players with limited information specific to female softball players. Objective: To determine between-limb differences in shoulder ROM and strength in healthy collegiate softball players. Design: Descriptive laboratory study. Setting: University research laboratory and collegiate athletic training room … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Only one other study has used the ASH test to examine shoulder strength in throwing athletes and found no significant differences bilaterally. 9 Potential explanations for the conflicting results may lie in the positioning utilized for the modified version of the ASH test and from player types. Biaggi et al 9 examined subjects in supine positioning rather than prone as the ASH test is typically performed and included players from all fielding positions, rather than pitchers alone.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Only one other study has used the ASH test to examine shoulder strength in throwing athletes and found no significant differences bilaterally. 9 Potential explanations for the conflicting results may lie in the positioning utilized for the modified version of the ASH test and from player types. Biaggi et al 9 examined subjects in supine positioning rather than prone as the ASH test is typically performed and included players from all fielding positions, rather than pitchers alone.…”
Section: Discussionmentioning
confidence: 99%
“…9 Potential explanations for the conflicting results may lie in the positioning utilized for the modified version of the ASH test and from player types. Biaggi et al 9 examined subjects in supine positioning rather than prone as the ASH test is typically performed and included players from all fielding positions, rather than pitchers alone. This study utilized pitchers only and the prone position for the purpose of isolation of shoulder strength in dedicated OH throwing-specific athletes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Usually, the YBT–UQ is recorded for both sides, thus inter-limb differences (i.e., asymmetry) can be detected as well as their association with athletic performance ( 7 ). In the first case, most of the available studies did not detect side differences in swimming ( 5 , 8 , 9 ) or in other sports like baseball ( 10 , 11 ) and softball ( 10 , 12 ). However, these studies were almost exclusively performed with adult athletes, which limits the transferability of the findings to young athletes due to growth, maturation, and development processes ( 13 ).…”
Section: Introductionmentioning
confidence: 90%